Manajemen Blended Learning Pasca Pandemi Covid-19: Studi Kasus Sekolah di Indonesia - Irwanto, Irwanto; Arifin, Zainal; Artanto, Dicky; Wahyuni, Titi; Jannah, Wardatul (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to find out the main factors that contribute to blended learning management in Indonesia. The research is focused on identifying the management process which includes, planning, organizing, implementing, and evaluating the blended learning management program at SMAN 2 Jember, SMKN 1 Wanayasa Banjarnegara and SMP 1 Prambanan Yogyakarta. This research is qualitative descriptive research with a naturalistic approach. The results show that the four functions of the management process have a very large influence on the results of the blended learning management program. First, the planning of the blended learning program involves all school stakeholders, as well as through the creation of a regular schedule. Second, in terms of organizing blended learning programs, the school goes through the curriculum work process so that teachers fill out a daily journal, to monitor activities. Third, the implementation of the blended learning program based on the learning process in the classroom by providing materials and explanations, as well as information transformation through room meeting to do practice questions at home. Fourth, learning evaluation is carried out through google classroom for attitude knowledge, and practicum for skill aspects, as well as private universities and UAS. Blended learning management policies involving all school stakeholders, filling out daily journals, learning in the classroom and delivering material through room meetings can optimize the learning process in the post-covid-19 pandemic period.